2020
DOI: 10.1037/adb0000497
|View full text |Cite
|
Sign up to set email alerts
|

Capacity of juvenile probation officers in low-resourced, rural settings to deliver an evidence-based substance use intervention to adolescents.

Abstract: Substance use is a major public health problem with a host of negative outcomes. Justice-involved youth have even higher risks and lack access to evidence-based interventions, particularly in rural communities. Task-shifting, or redistribution of tasks downstream to an existing workforce with less training, may be an innovative strategy to increase access to evidence-based interventions. Initial findings are presented from a services research trial conducted primarily in rural communities in which an existing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…In the present study, this approach was used to accommodate the still-developing capacities of adolescents to shape their behavior to achieve long-term goals by breaking tasks into short-term, weekly assignments. Our study's findings also add support to the feasibility and benefit of implementing contingency-like schedules into juvenile probation routines (Schwalbe, 2012;Sheidow et al, 2020). While other studies have found positive outcomes of implementing contingency schedules on recidivism in adult probation (Rudes et al, 2012;Trotman & Taxman, 2011), this study demonstrates the benefit of a contingency-like schedule on youth recidivism as well.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In the present study, this approach was used to accommodate the still-developing capacities of adolescents to shape their behavior to achieve long-term goals by breaking tasks into short-term, weekly assignments. Our study's findings also add support to the feasibility and benefit of implementing contingency-like schedules into juvenile probation routines (Schwalbe, 2012;Sheidow et al, 2020). While other studies have found positive outcomes of implementing contingency schedules on recidivism in adult probation (Rudes et al, 2012;Trotman & Taxman, 2011), this study demonstrates the benefit of a contingency-like schedule on youth recidivism as well.…”
Section: Discussionsupporting
confidence: 78%
“…The model highlights the importance of youth experiencing success shortly after initiating probation, progress over perfection, and increased interaction with positive peer groups. Two recent studies found behavioral modification using positive reinforcement in juvenile probation was acceptable to probation officers (Rudes et al, 2021; Sheidow et al, 2020). Sheidow and colleagues (2020) found that juvenile probation officers trained in contingency management (i.e., a behavior modification approach using reinforcement principles) were able to deliver this approach as well or better than trained psychotherapists.…”
Section: Prior Incorporation Of Adolescent Developmental Science Into...mentioning
confidence: 99%
See 1 more Smart Citation
“…The four articles in this section represent diverse research designs, from a randomized trial to a theoretical review. The first study (Sheidow, McCart, Chapman, & Drazdowski, 2019) randomized juvenile probation officers (JPOs) to either learn and deliver family-based CM or to continue to deliver probation as usual (PAU). Results supported the high feasibility of training JPOs to deliver CM as they showed greater implementation of CM than those assigned to PAU and comparable to (and in some comparisons better than) trained clinicians in a prior study.…”
Section: Special Issue Topics and Articlesmentioning
confidence: 99%
“…When resources are limited, the responsibility of conducting brief interventions may be assigned to nonclinical staff (Christl et al., 2010; Sharp, Pineros, Hsu, Starks, & Sales, 2004). Often called task shifting, this practice has been used to lighten the workload of clinicians and other providers (O'Neil et al., 2019) and has recently been expanded to JJ settings (Sheidow, McCart, Chapman, & Drazdowski, 2020). It has been recommended that nonclinical staff and JJ stakeholders (e.g., probation officers, bachelor’s level social workers, legal professionals, etc.)…”
Section: Introductionmentioning
confidence: 99%